Influence of normograde versus retrograde catheterization of bile ducts in dogs treated for gallbladder mucocele. Issue 4 (1st April 2021) - Putterman, Allison B.; Selmic, Laura E.; Kindra, Cameron; Duffy, Daniel J.; Risselada, Marije; Phillips, Heidi
Abstract: Objective: To determine the influence of normograde (NG) versus retrograde (RG) catheterization of the cystic duct and common bile duct (CBD) in dogs with gallbladder mucoceles (GBM) treated with open cholecystectomy. Study design: Retrospective study. Animals: Dogs ( n = 117) with GBM. Methods: Medical records were reviewed for signalment, history, clinical laboratory and diagnostic imaging findings, details of surgery including catheterization method, complications, and outcome. Long‐term follow‐up data were obtained by telephone or electronic communication. Relationships between catheterization method and clinical variables and outcome were evaluated. Results: Dogs catheterized RG were more likely to experience any postoperative complication ( p = .0004) including persistence of gastrointestinal signs ( p = .0003). Survival to discharge and long‐term survival did not differ by group ( p = .23 and p = .49). Total bilirubin (TB) decreased by 70.3% after NG catheterization compared to 39.1% after RG catheterization ( p = .03) and increased in 14.9% dogs catheterized NG and 38.0% dogs catheterized RG ( p = .004). The presence of a diplomate surgeon at surgery resulted in decreased incidences of any perioperative or postoperative complication ( p = .003 and p = .05). Conclusion: Retrograde catheterization was associated with more postoperative concerns than NG catheterization, but similar survival times. Surgery should be performed by diplomates experienced in biliary surgery to minimize complications. Clinical significance: Although both NG and RG techniques to catheterize the cystic duct and CBD are options for treatment of GBM with low mortality, results of this study provide some evidence to recommend NG over RG catheterization.